To tame a cowboy - Hedlund, Jody (Hedlund, Jody. Colorado cowboys, 2022)
"When Savannah's family and the resentments of the area cattleman catch up with them both, Brody and Savannah will have to tame their fears if they've any hope to let love run free"--